EFFECTS OF AZADIRACHTIN ON DEVELOPMENT OF MODEL INSECT_x000D_ Galleria mellonella L. (LEPIDOPTERA: PYRALIDAE) - (:unkn) unknown (My University, 2019)
Azadirachtin (AZA), a plant allelochemical, is used against pest organisms and Lepidopteran species are quite sensitive tothis substance. In this study, the developmental effects of AZA on model insect and greater wax moth, Galleria mellonella L.(Lepidoptera: Pyralidae) larvae via force feeding method were investigated. To investigate the effects of different doses ofpure AZA (0.2 - 5 µg/larva), seventh instar larvae were fed by a force feeding method. The results showed that all doses ofAZA caused lethal and sublethal effects on the biological parameters of G. mellonella. Larval developmental time increasedwhile that of pupa did not change depending on the increasing doses of AZA. In addition, adult longevity, and weights ofpupae and adults decreased at all AZA doses in a dose-dependent manner. In conclusion, this study, using G. mellonella as amodel organism, showed that AZA has insecticidal activity and causes adverse effects on the life history traits ofLepidopteran pest insects.